2019
DOI: 10.3389/fgene.2019.01144
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Genetic Variants Alter Their Secondary Structure and Expression in Patients With RASopathies Syndromes

Abstract: RASopathies are a group of rare genetic diseases caused by germline mutations in genes involved in the RAS–mitogen-activated protein kinase (RAS-MAPK) pathway. Whole-exome sequencing (WES) is a powerful approach for identifying new variants in coding and noncoding DNA sequences, including miRNAs. miRNAs are fine-tuning negative regulators of gene expression. The presence of variants in miRNAs could lead to malfunctions of regulation, resulting in diseases. Here, we identified 41 variants in mature miRNAs throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 82 publications
1
6
0
1
Order By: Relevance
“…We overlapped the identified miRNA variant sites with dbSNP version151 (All SNPs) followed by exome data to filter out variations at the DNA level. However, it is worthwhile to note here that these variations (genome encoded) can still be in the resulting transcript (miRNA) and bring out possible functional consequences [54,55]. Further, all A-to-C modifications were excluded from the analysis due to specific biases of Illumina sequencers [56,57].…”
Section: Resultsmentioning
confidence: 99%
“…We overlapped the identified miRNA variant sites with dbSNP version151 (All SNPs) followed by exome data to filter out variations at the DNA level. However, it is worthwhile to note here that these variations (genome encoded) can still be in the resulting transcript (miRNA) and bring out possible functional consequences [54,55]. Further, all A-to-C modifications were excluded from the analysis due to specific biases of Illumina sequencers [56,57].…”
Section: Resultsmentioning
confidence: 99%
“…The diabetic neuropathy including cardiovascular autonomic neuropathy (CAN) and diabetic neuropathy (DPN) have been reported to impact the quality of life in diabetics since these complications have been reported in a large percentage of diabetics. The miR-499a is an antiapoptotic and cardioprotective miRNA ( Wang et al, 2011 ; de Carvalho et al, 2019 ). It has been reported that polymorphisms in miR499 are involved in perturbed insulin secretion, CAN, and peripheral neuropathy ( Ciccacci et al, 2018 ).…”
Section: Snps In Seed Sequence Of Mirna and The 3′utr Of Specific Target Genes In Diabetesmentioning
confidence: 99%
“…Для шести из данных микроРНК описаны гены мишени из киназного пути RAS-MAPK. Для четырех микроРНК было показано изменение дифференциальной экспрессии по сравнению с контрольной группой здоровых людей [50]. Для изучения влияния данных вариантов в генах микроРНК на патогенез РАСопатий необходимы дальнейшие исследования.…”
Section: патогенез заболеваний вызванных мутациями в генах микрорнкunclassified